PEMBERIAN PROGRAM LATIHAN BALLANCE EXERCISE TERHADAP KESEIMBANGAN KLIEN LANSIA DI KELURAHAN 23 ILIR PALEMBANG - Ikop, Ridwan; Sulaiman, Sulaiman; Martini, Sri (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Increased morbidity cases in the elderly have caused health status problems for clients, especially the elderly. Promotive efforts through the Ballance excercise  training program excerises as well as being very important for clients to improve their health status. This study aims to obtain a picture of the effectiveness of Ballance Excerise  on the Ballance of the body's health in the elderly. The research design used was quasi experiment with pretest-posttest design, sampling strategy using random sampling with a sample size of 40 for the statistical test used was the T test . found there are differences in the average before and after giving Ballance Excise with p value 0,000, there is no relationship between sex with the training program with a p value of 0.351, there is no relationship between work with the training program with a p value of 0.262, there is a relationship between educational work and the training program with a p value of 0.010, there was no relationship between body weight with an exercise program with a p value of 0.735, and there was a relationship between age with an exercise program with a p value of 0.006. The results can be used as a basis for policy makers and health service managers in the context of implementing complementary therapies to increase community empowerment and can be replicated in various health care settings, especially in the elderly